Graphene/fluorescein dye-based sensor for detecting As(III) in drinking water - Madhu D. Sharma (Nature Portfolio, 2021)
Abstract A complex of reduced graphene oxide (rGO) and fluorescein (FL) dye nanoparticles of size between 50 and 100 nm has been prepared and its sensing performance for detection of As(III) in drinking water has been reported. When As(III) binds to the rGO–FL nanoparticles the relative quenching of fluorescence was increased with increase in As(III) concentration thus provide two linear calibration ranges (0–4.0 mmol L−1 and 4.0–10 mmol L−1). The fluorescence quenching mechanism was investigated by using time-resolved fluorescence spectroscopy and molecular modeling. The detection limit of this sensor has been determined as equal to 0.96 µg L−1 which is about 10 times lower than the WHO stipulated standard for As(III) in drinking water (10 µg L−1). The analytical performance and potential application of the nanosensor was compared to commercial field kits used in arsenic monitoring. The sensor proposed in this study is fast, sensitive and accurate for detection of As(III) in drinking water and environmental samples.